2015
DOI: 10.4172/2157-7110.1000475
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties and Preparation of Diet Apricot Jam

Abstract: This research was conducted to prepare apricot diet jam from the pulp of fresh mature apricots by using artificial sweeteners i.e. aspartame and saccharine. Apricots were washed with clean water to remove dust particles. After sorting and pitting, apricots were cut into two halves with the help of stainless steel knives and dipped in 0.1% citric acid solution to avoid browning. The pulp of apricots was extracted by using plumper. Apricot pulp was heated to get the desired consistency. Low heating was continued… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
1
1
Order By: Relevance
“…pH of the fruit sample is very important, as it help in the formation of optimum gel in the preparation of jam. In contrast, the pH value of apple and apricot jam studied by Anjum et al [16] were found to be somewhat higher than present findings. The raise in acidity of jam samples during storage period resulted from the formation of acidic compound resulted in the decrease of pH.…”
Section: Sample Preparationcontrasting
confidence: 96%
See 1 more Smart Citation
“…pH of the fruit sample is very important, as it help in the formation of optimum gel in the preparation of jam. In contrast, the pH value of apple and apricot jam studied by Anjum et al [16] were found to be somewhat higher than present findings. The raise in acidity of jam samples during storage period resulted from the formation of acidic compound resulted in the decrease of pH.…”
Section: Sample Preparationcontrasting
confidence: 96%
“…The observed value of reducing sugars of the jam samples from CA 0 to CA 5 at initial day were 16 Tables 4 and 5) . The analysis of reducing sugar of strawberry jam during storage interval showed an increasing trend [19], hence justifying the present results.…”
Section: Reducing Sugarmentioning
confidence: 93%